Diagnosis of comorbid migraine without aura in patients with idiopathic/genetic epilepsy based on the gray zone approach to the International Classification of Headache Disorders 3 criteria - Atalar, Arife Çimen; Özge, Aynur; Türk, Bengi Gül; Ekizoğlu, Esme; Kurt Gök, Duygu; Baykan, Betül; Ayta, Semih; Erdoğan, Füsun Ferda; Yeni, Seher Naz; Taşdelen, Bahar; , IDEM Study Group; Velioğlu, Sibel K.; et al. (Frontiers in Neurology, 2023)
Background: Migraine without aura (MwoA) is a very frequent and remarkable comorbidity in patients with idiopathic/genetic epilepsy (I/GE). Frequently in clinical practice, diagnosis of MwoA may be challenging despite the guidance of current diagnostic criteria of the International Classification of Headache Disorders 3 (ICHD-3). In this study, we aimed to disclose the diagnostic gaps in diagnosis of comorbid MwoA, by using a zone concept, in patients with I/GEs with headache who were diagnosed by an experienced headache expert. Methods: In this multicenter study including 809 consecutive patients with a diagnosis of I/GE with or without headache, 163 patients who were diagnosed by an experienced headache expert as having a comorbid MwoA were re-evaluated. Eligible patients were divided into three subgroups: full diagnosis, zone I, and II according to their status of fulfilling the ICHD-3 criteria. Classification and Regression Tree (CART) analysis was performed to bring out the meaningful predictors when evaluating patients with I/GEs for MwoA comorbidity, using the variables that were significant in the univariate analysis. Results: Longer headache duration (˃4 hours) followed by throbbing pain, higher visual analog scale (VAS) scores, increase of pain by physical activity, having nausea/vomiting, photo and /or phonophobia are the main distinguishing clinical characteristics of comorbid MwoA in I/GE patients, for being classified in the full diagnosis group. Despite being not a part of the main ICHD-3 criteria, the presence of associated symptoms mainly osmophobia and also vertigo/dizziness had distinguishing capability in being classified into zone subgroups. The most common epilepsy syndromes fulfilling full diagnosis criteria (n=62) in the CART analysis were 48.39% Juvenile myoclonic epilepsy followed by 25.81% Epilepsy with Generalized Tonic-Clonic Seizures Alone . Conclusions: Longer headache duration, throbbing pain, increase of pain by physical activity, photo and/or phonophobia, presence of vertigo/dizziness, osmophobia, and higher VAS scores are the main supportive associated factors when applying the ICHD-3 criteria for the comorbid MwoA diagnosis in patients with I/GEs. Evaluating these characteristics could be helpful to close the diagnostic gaps in the everyday clinical practice and fasten the diagnosic process of comorbid MwoA in patients with I/GEs.